Urea cycle disorders in Spain: an observational, cross-sectional and multicentric study of 104 cases - Martín-Hernández, Elena; Aldámiz-Echevarría, Luis; Castejón-Ponce, Esperanza; Pedrón-Giner, Consuelo; Couce, María Luz; Serrano-Nieto, Juliana; Pintos-Morell, Guillem; Bélanger-Quintana, Amaya; Martínez-Pardo, Mercedes; García-Silva, María Teresa; Quijada-Fraile, Pilar; Vitoria-Miñana, Isidro; et al. (Orphanet journal of rare diseases, 2014)
Background Advances in the diagnosis and treatment of urea cycle disorders (UCDs) have led to a higher survival rate. The purpose of this study is to describe the characteristics of patients with urea cycle disorders in Spain. Methods Observational, cross-sectional and multicenter study. Clinical, biochemical and genetic data were collected from patients with UCDs, treated in the metabolic diseases centers in Spain between February 2012 and February 2013, covering the entire Spanish population. Heterozygous mothers of patients with OTC deficiency were only included if they were on treatment due to being symptomatic or having biochemistry abnormalities. Results 104 patients from 98 families were included. Ornithine transcarbamylase deficiency was the most frequent condition (64.4%) (61.2% female) followed by type 1 citrullinemia (21.1%) and argininosuccinic aciduria (9.6%). Only 13 patients (12.5%) were diagnosed in a pre-symptomatic state. 63% of the cases presented with type intoxication encephalopathy. The median ammonia level at onset was 298 μmol/L (169-615). The genotype of 75 patients is known, with 18 new mutations having been described. During the data collection period four patients died, three of them in the early days of life. The median current age is 9.96 years (5.29-18), with 25 patients over 18 years of age. Anthropometric data, expressed as median and z-score for the Spanish population is shown. 52.5% of the cases present neurological sequelae, which have been linked to the type of disease, neonatal onset, hepatic failure at diagnosis and ammonia values at diagnosis. 93 patients are following a protein restrictive diet, 0.84 g/kg/day (0.67-1.10), 50 are receiving essential amino acid supplements, 0.25 g/kg/day (0.20-0.45), 58 arginine, 156 mg/kg/day (109-305) and 45 citrulline, 150 mg/kg/day (105-199). 65 patients are being treated with drugs: 4 with sodium benzoate, 50 with sodium phenylbutyrate, 10 with both drugs and 1 with carglumic acid. Conclusions Studies like this make it possible to analyze the frequency, natural history and clinical practices in the area of rare diseases, with the purpose of knowing the needs of the patients and thus planning their care.